Musculoskeletal pain and musculoskeletal syndromes in adolescents are related to electronic devices - Lígia Bruni Queiroz; Benito Lourenço; Luiz Eduardo Vargas Silva; Daniela Mencaroni Rodrigues Lourenço; Clovis Artur Silva (Elsevier, 2018)
Objective: To evaluate television and simultaneous electronic devices use in adolescents with musculoskeletal pain and musculoskeletal pain syndromes. Methods: A cross-sectional study was performed in 299 healthy adolescents of a private school. All students completed a self-administered questionnaire, including: demographic data, physical activities, musculoskeletal pain symptoms, and use of simultaneous television/electronic devices (computer, internet, electronic games, and cell phones). Seven musculoskeletal pain syndromes were also evaluated: juvenile fibromyalgia, benign joint hypermobility syndrome, myofascial syndrome, tendinitis, bursitis, epicondylitis, and complex regional pain syndrome. Results: Inter-rater agreement between pretest and retest was 0.83. Musculoskeletal pain and musculoskeletal pain syndrome were found in 183/299 (61%) and 60/183 (33%), respectively. The median age (15 [10-18] vs. 14 [10-18] years, p = 0.032) and years of education (10 [5-12] vs. 9 [5-12] years, p = 0.011) were significantly higher in adolescents with musculoskeletal pain when compared with those without this condition. The frequencies of female gender (59% vs. 47%, p = 0.019), cell phone use (93% vs. 81%, p = 0.003), and simultaneous use of at least two electronic devices (80% vs. 67%, p = 0.011) were significantly higher in the former group. Further comparisons between adolescents with and without musculoskeletal pain syndromes revealed that the frequency of female gender was significantly higher in the former group (75% vs. 25%, p = 0.002), and with a significantly reduced median of weekends/holidays electronic games use (1.5 [0-10] vs. 3 [0-17] h/day, p = 0.006). Conclusions: A high prevalence of musculoskeletal pain/syndromes was observed in female adolescents. Musculoskeletal pain was mostly reported at a median age of 15 years, and students used at least two electronic devices. Reduced use of electronic games was associated with musculoskeletal pain syndromes. Resumo: Objetivo: Avaliar o uso de televisão e dispositivos eletrônicos em adolescentes com dor e síndromes musculoesqueléticas. Métodos: Foi feito um estudo transversal com 299 adolescentes saudáveis de uma escola particular. Todos os alunos responderam a um questionário autoaplicável, que incluiu perguntas sobre: dados demográficos, prática de atividade física, sintomas de dor musculoesquelética e o uso de televisão/ dispositivos eletrônicos (computador, internet, jogos eletrônicos e celular). Sete síndromes musculoesqueléticas foram avaliadas: fibromialgia juvenil, síndrome de hipermobilidade articular benigna, síndrome miofascial, tendinite, bursite, epicondilite e síndrome de dor regional complexa. Resultados: A concordância entre o pré-teste e reteste foi de 0,83. Dor musculoesquelética e síndromes musculoesqueléticas foram encontradas em 183/299 (61%) e 60/183 (33%), respectivamente. As medianas de idade [15 (10-18) versus 14 (10-18) anos, p = 0,032] e de anos de escolaridade [10 (5-12) vs. 9 (5-12) anos, p = 0,010] foram significantemente maiores em adolescentes com dor musculoesquelética em comparação com aqueles sem essa condição. As frequências do sexo feminino (59% versus 47% p = 0,019), uso do telefone celular (93% contra 81%, p = 0,003) e do uso simultâneo de pelo menos dois dispositivos eletrônicos (80% vs. 67%, p = 0,011) foram significantemente maiores no grupo de adolescentes com dor musculoesquelética. Comparações adicionais entre os adolescentes com e sem síndromes musculoesqueléticas revelaram que a frequência do sexo feminino foi significantemente maior no primeiro grupo de (75% versus 25%, p = 0,002), e com mediana significantemente reduzida de horas de jogos eletrônicos aos finais de semana e feriados [1,5 (0-10) vs. 3 (0-17) horas/dia, p = 0,006]. Conclusões: Uma alta prevalência de dor/síndromes musculoesqueléticas foi observada em adolescentes do sexo feminino. A dor musculoesquelética foi predominantemente relatada entre alunos com mediana de idade de 15 anos e que usavam pelo menos dois dispositivos eletrônicos simultaneamente. O uso reduzido de jogos eletrônicos foi associado à presença de síndromes musculoesqueléticas. Keywords: Adolescent, Musculoskeletal pain, Musculoskeletal pain syndromes, Electronic devices, Palavras-chave: Adolescente, Dor musculoesquelética, Síndromes musculoesqueléticas, Dispositivos eletrônicos